Thermo-electrical performance of PEM fuel cell using Al2O3nanofluids - Irnie, Zakaria; W. A. N. W., Mohamed; Azmi, W. H.; A. M. I., Mamat; R., Mamat; W. R. W., Daud (Elsevier Ltd., 2018)
Nanofluid adoption as an alternative coolant for Proton Exchange Membrane (PEM) fuel cell is a new embarkation which hybridizes the nanofluids and PEM fuel cell studies. In this paper, findings on the thermo-electrical performance of a liquid-cooled PEM fuel cell with the adoption of Al2O3 nanofluids were established. Thermo-physical properties of 0.1, 0.3 and 0.5% volume concentration of Al2O3 nanoparticles dispersed in water and water: Ethylene glycol (EG) mixtures of 60:40 were measured and then adopted in PEM fuel cell as cooling medium. The result shows that the cooling rate improved up to 187% with the addition of 0.5% volume concentration of Al2O3 nanofluids to the base fluid of water. This is due to the excellent thermal conductivity property of nanofluids as compared to the base fluid. However, there was a penalty of higher pressure drop and voltage drop experienced. Thermo electrical ratio (TER) and Advantage ratio (AR) were then established to evaluate the feasibility of Al2O3 nanofluid adoption in PEM fuel cells in terms of both electrical and thermo-fluid performance considering all aspects including heat transfer enhancement, fluid flow and PEM fuel cell performance. Upon analysis of these two ratios, 0.1% volume concentration of Al2O3 dispersed in water shows to be the most feasible nanofluid for adoption in a liquid-cooled PEM fuel cell.